'Kingsman', Not 'My Fair Lady:' Dialect and Stereotype in the Films 'The Secret Service' and 'The Golden Circle' - Carla Soares (Anglo Saxonica)
The way characters in film are portrayed, through dress code, behaviour and speech, is often revealing of social patterns and social critique, independently from the film genre or the target audience. This article focuses on the portrayal of lead and supporting actors in the two instalments of Kingsman, The Secret Service and The Golden Circle (2014 and 2017 respectively, both by Mathew Vaughn), departing, in the first case, from a Pygmalionesque transformative idea and, centered in Harry/Galahad’s (Colin Firth) motto “Manners Maketh Man” to partially portray social context in Britain and extending its “tongue-in-cheek” critique to the American Southern culture in The Golden Circle, in purposely biased portraits. The emphasis is on how dialect, particularly accent, aid in the construction or deconstruction of stereotypes, both in British and North American contexts, and how they reflect particular views of the world(s).